Pelaksanaan Pembelajaran IPS Berbasis Lingkungan Alam Sekitar Sekolah Sebagai Sumber Belajar di MTsN Padang Panjang - Tiara Nistia (Universitas Islam Raden Rahmat Malang, 2025)
This study aims to analyze the implementation of social studies learning based on the natural environment around the school as a learning resource at MTsN Padang Panjang. The background of this study is the lack of interest and enthusiasm for learning social studies of students which is triggered by various factors, one of which is the underutilization of the environment around the school as a learning resource. The research method is a qualitative approach, data collection tools through observation, interviews and documentation. The results of the study show that the implementation of social studies learning based on the natural environment around the school is carried out through 3 stages. Preliminary Activities: Educators make preparations that begin with an opening greeting, checking attendance, apperception, providing motivation, providing references and dividing students into several groups, Core Activities: Educators explain a little related material, students make direct observations in the field, presentations of findings and projects, and Closing Activities Reflecting and evaluating learning and closing learning with praying together and a message to always protect the environment